Cardiac adaptation to acute and chronic participation in endurance sports. Issue 24 (5th November 2011) - George, Keith; Spence, Angela; Naylor, Louise H; Whyte, Gregory P; Green, Daniel J
Abstract : The pervasive public health message is that moderate amounts of endurance exercise help maintain optimal health and reduce cardiovascular risk. While not enough people meet national physical activity guidelines, there are some at the opposite end of the activity spectrum who far exceed the recommended 'dose' of exercise. The cardiovascular health consequences of single and/or multiple (lifelong) 'doses' of high-volume endurance exercise are currently being debated. Recent commentaries, case reports and case series data have posed the question whether you can 'overdose on exercise', and that is the focus of this brief review.